The impact of continuous renal replacement therapy for metabolic disorders in infants - Fatih Aygun; Deniz Aygun; Firuze Erbek Alp; Tanyel Zubarıoglu; Cigdem Zeybek; Halit Cam (Elsevier, 2018)
Background: While Continuous Renal Replacement Therapy (CRRT) is a well established treatment modality for patients with acute kidney insufficiency (AKI), it is now also being used for the management of various illnesses such as acute metabolic disorders presenting with hyperammonemia and elevated leucine levels. Herein, we aimed to describe our experience with CRRT in treatment of acute decompensation of 14 patients with a diagnosis of metabolic disorder who has been admitted to our pediatric intensive care unit (PICU) in the last year. Methods: Patients who have had life threatening acute metabolic crisis due to various metabolic disorders and were treated with continuous renal replacement therapy (CRRT) were evaluated retrospectively. Results: Between November 2014 and December 2015, 14 patients were found to have received CRRT for various metabolic disorders in the PICU. Ten patients had hyperammonemia and four patients had elevated leucine levels. Nine patients were male and five were female. The age interval was between 2 days and 18 months, with a mean of 5.5 ± 7.4 months. The weight distribution was between 2.5 and 18 kg, with a mean of 7.3 ± 5.6 kg. Eleven patients received continuous veno-venous hemodiafiltration (CVVHDF), and 3 patients with MSUD received continuous veno-venous hemodialysis (CVVHD). All patients have received high throughput hemodialysis and hemofiltration. The dialyzate rate was set to be minimum 4042 ml/h/1.73 m2, and maximum 12,900 ml/h/1.73 m2. Hemofiltration was performed with a replacement rate of 40-76 ml/kg/h. The average CRRT duration was 16.6 ± 15.6 h. Conclusions: We suggest that CRRT is an efficient method that can be used in hyperammonemia and elevated leucine levels which are metabolic emergencies.